IMPLEMENTASI KEBIJAKAN PENATAAN PKL DI KAWASAN ALUN-ALUN SIMPANG TUJUH KABUPATEN KUDUS - Laras Hapsari; Hesti Lestari; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2023)
The Simpang Tujuh Square area is a red zone area for street vendors. Before there was a regent regulation, the area was a yellow zone, so the area was full of street vendors. This study aims to identify and analyze the implementation of street vendor management policies in Simpang Tujuh Square Area, Kudus Regency, and the factors that support or hinder the implementation of street vendor management policies. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The results of the study show that the implementation of the street vendor arrangement policy in the Simpang Tujuh Square area has not been carried out properly. There are some activities whose implementation is not yet good, namely structuring activities and monitoring activities, while street vendor development activities carried out by the Kudus Regency Trade Office have been going well. Based on the results of the analysis of the implementation of the PKL structuring policy, it can be seen that the compliance level of implementing actors in structuring street vendors in the Simpang Tujuh Square area, Kudus Regency, has not been maximized. Regarding the smooth running of routines or activities in the implementation of the PKL structuring policy, there are still obstacles, so there are activities that cannot be carried out. Regarding the expected performance and impact, it shows that the performance in implementing the street vendor arrangement policy in the Simpang Tujuh Square area is shown to be in line with the impacts faced, both negative and positive impacts. Factors that support policy implementation, namely communication, bureaucratic structure, and attitude of implementers, while factors that hinder namely resources and economic environment.